Habitat characteristics or protected area size: What is more important for the composition and diversity of mammals in nonprotected areas?. Issue 12 (1st May 2021) - Li, Wenbo; Yang, Peipei; Li, Bowen; Liu, Chao; Sun, Lixing; Li, Jinhua
Abstract: The margins of protected areas are usually considered to have greater forest degradation, and given that most mammals live outside protected areas, researchers and conservation practitioners are increasingly recognizing that nonprotected areas must be incorporated into conservation strategy. However, the strategy used to manage these areas still involves increasing the size of protected areas, while not considering the habitat characteristics and requirements of the species. In this study, during a 3‐year period, camera trap and habitat characteristic surveys were used to estimate composition, diversity, and habitat characteristics of mammals to determine habitat characteristics or increase the size of protected areas what should be considered first for mammals' conservation in a nonprotected area near the Huangshan Mountains in Anhui Province, China. From June 2017 to October 2019, 18 species of mammals were recorded, more than in any other protected area nearby. The linear model analysis results showed that habitat characteristics of mammals were different and showed a significant correlation with their relative abundance. Most species were related to vegetation characteristics, except primates ( Macaca thibetana ), and rodents ( Leopoldamys edwardsi ). Therefore, to establish conservation policies for nonprotected areas, habitat characteristics should be of prime concern, followed by increasing the size of protected areas to provide effective refuge areas for species conservation. Abstract : Very few studies (and that too lacking systematic and serious research efforts) have been done in areas surrounding protected areas and natural reserves. There are many knowledge gaps in the understanding of variations in communities or assemblages of mammals in unprotected subtropical forests near protected area boundaries. This study investigated this gap in knowledge.